2019
DOI: 10.4314/ovj.v9i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Bladder teratoma in a maned wolf (<i>Chrysocyon brachyurus</i>)

Abstract: Background: Teratomas are germ cell tumors, comprised of a mixture of tissue types and with tissue foreign to their site of origin. Case Description: A 5.5-year-old intact female maned wolf (Chrysocyon brachyurus) was treated for recurrent stranguria and suspected cystitis. Due to lack of resolution, the wolf was anesthetized for further evaluation. The urinary bladder was firm on palpation, with a markedly thickened wall and no observable lumen on ultrasound. Neoplastic infiltration was suspected on double co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…(2013) in the ultrasound evaluations performed on five adult individuals, where they also refer to the difficulty in visualising the non‐gravid uterus. Another work reports a bladder teratoma found through ultrasound evaluation (Fox et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) in the ultrasound evaluations performed on five adult individuals, where they also refer to the difficulty in visualising the non‐gravid uterus. Another work reports a bladder teratoma found through ultrasound evaluation (Fox et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The measurements obtained in the present case with regard to the thickness of the stomach walls (Figure 5) and the average thickness of the intestines, as well as the contents of the gall bladder (Figure 4), match the measurements reported by Guimarães et al (2013) in the ultrasound evaluations performed on five adult individuals, where they also refer to the difficulty in visualising the non-gravid uterus. Another work reports a bladder teratoma found through ultrasound evaluation (Fox et al, 2019).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that most of these neoplasms derive from anomalies in the ectodermal layer and in a minority from the endodermal layer. Teratomas can be classified as mature and immature based on cell differentiation, therefore they can consist of different mature and immature tissues derived from the three layers of germ cells [ 9 ]. Testicular cancer accounts for only 1% of malignant tumors in both humans and animals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 The species is listed as near-threatened by the IUCN. 11 Information regarding neoplastic diseases in maned wolves is scarce and mainly restricted to a few case reports, such as mammary tumors, 6 pancreatic gastrinoma, 5 bladder teratoma, 8 and ovarian tumors. 2,15 Dysgerminoma is among the most common ovarian tumor in this species, and this high prevalence is suspected to be the result of a hereditary predisposition.…”
mentioning
confidence: 99%